2000
DOI: 10.1001/archpedi.154.7.657
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Study on the Effectiveness of a Multifaceted Intervention Program in the Primary Prevention of Asthma in High-Risk Infants

Abstract: Background:The prevalence of asthma has increased in developed countries in the past 2 decades. The effectiveness of intervention measures on the primary prevention of asthma has not been well studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
139
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(145 citation statements)
references
References 23 publications
3
139
1
2
Order By: Relevance
“…A major limitation is the fact that most of the environmental exposure-reducing measures, including breastfeeding, weaning practices, procuring pets and smoking, cannot be blindly executed. All birth cohort intervention studies experience this problem [17,20]. Therefore, reporting bias cannot be excluded as an explanation for the decrease in asthma-like symptoms in the intervention group at age 2 yrs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A major limitation is the fact that most of the environmental exposure-reducing measures, including breastfeeding, weaning practices, procuring pets and smoking, cannot be blindly executed. All birth cohort intervention studies experience this problem [17,20]. Therefore, reporting bias cannot be excluded as an explanation for the decrease in asthma-like symptoms in the intervention group at age 2 yrs.…”
Section: Discussionmentioning
confidence: 99%
“…Several randomised intervention studies have reported results on various clinical symptoms at age 1 [17,20,34], 2 [18,35], 3 [36], 4 [37] and 8 yrs [19]. When the results of intervention studies are compared, it has to be kept in mind that comparison is hampered, as the studies differ in defining high-risk cases, the applied intervention(s) and the definition of outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most successful programs are those that have combined environmental interventions with face-to-face education over multiple home visits. 7,[17][18][19][20][21] …”
mentioning
confidence: 99%
“…As to the effect of exposure on the development of asthma in infancy, the proof of the pudding will lie in controlled trials with randomised reduction of allergen exposure in birth cohorts. There are many ongoing randomised clinical trials but only a few of these with sufficient follow-up have thus far been published: the Isle of Wight study [12], a Canadian multifaceted intervention program in high-risk infants [13] and the NAC-MAAS study [14]. These three studies all investigated high-risk children (according to parental atopic status) and allocated them randomly to environmental manipulation in which several combined measures to reduce prenatal and postnatal allergen exposure were undertaken.…”
mentioning
confidence: 99%